Current and Future Global Lake Methane Emissions: A Process‐Based Modeling Analysis. Issue 3 (23rd March 2023) - Zhuang, Qianlai; Guo, Mingyang; Melack, John M.; Lan, Xin; Tan, Zeli; Oh, Youmi; Leung, L. Ruby
Abstract: Freshwater ecosystem contributions to the global methane budget remains the most uncertain among natural sources. With warming and accompanying carbon release from thawed permafrost and thermokarst lake expansion, the increase of methane emissions could be large. However, the impact and relative importance of various factors related to warming remain uncertain. Based on diverse lake characteristics incorporated in modeling and observational data, we calibrate and verify a lake biogeochemistry model. The model is then applied to estimate global lake methane emissions and examine the impacts of temperature increase for the first and the last decades of the 21st century under different climate scenarios. We find that current emissions are 24.0 ± 8.4 Tg CH4  yr −1 from lakes larger than 0.1 km 2, accounting for 11% of the global total natural source as estimated based on atmospheric inversion. Future projections under the RCP8.5 scenario suggest a 58%–86% growth in emissions from lakes. Our model sensitivity analysis indicates that additional carbon substrates from thawing permafrost may enhance methane production under warming in the Arctic. Warming enhanced methane oxidation in lake water can be an effective sink to reduce the net release from global lakes. Plain Language Summary: Methane is the second most important greenhouse gas after carbon dioxide but with much stronger warming potential. Providing accurate estimates and future projections of methane emissions are challenging but essential for supporting climate mitigation strategies. Freshwater ecosystems including lakes and reservoirs contribute large uncertainty in the quantification of global methane sources. In this study, with an improved lake modeling approach, we estimate global lake methane emissions and examine the impacts of temperature increase, permafrost thaw, and thermokarst lake area changes in the future. Our modeling suggests that the current magnitude and the future increase of global lake methane emissions are lower than previously suggested. Under warming conditions, the increase of methane oxidation reduces the net lake methane emissions. Key Points: Current global lake methane release estimated to account for 11% of the global total natural source emissions Future global lake emissions are estimated to increase 58%–86% under the severe climate warming scenario RCP8.5 Under warming conditions, methanogenesis will increase, but enhanced methane oxidation in water column can dampen the net methane emission